Toward charge extraction in all-inorganic perovskite solar cells by interfacial engineering. Issue 44 (21st May 2018) - Ding, Jie; Duan, Jialong; Guo, Chenyang; Tang, Qunwei
Abstract : CuInS2 /ZnS QDs with tunable bandgaps were applied at the CsPbBr3 /carbon interface for improved hole extraction and reduced electron–hole recombination. A PCE of as high as 8.42% was achieved for QDs tailored all-inorganic PSC in comparison with 6.01% for the pristine device. Abstract : All-inorganic perovskite solar cells (PSCs) are a promising solution to address the poor stability of organic–inorganic hybrid PSC devices under humidity and thermal attacks. However, the severe interfacial charge recombination from large energy differences has markedly limited the further enhancement of power conversion efficiency. The charge extraction from perovskite layer has been improved by setting intermediate energy levels using quantum dots (QDs) through interfacial engineering. In the current study, CuInS2 /ZnS QDs with tunable bandgaps and hole-transporting behavior were prepared to modify the CsPbBr3 /carbon interface. Arising from the improved charge separation, a power conversion efficiency of 8.42% was achieved for QD tailored inorganic PSC in comparison with 6.01% for pristine devices. These all-inorganic PSCs present unprecedented stability under high humidity and significant improvements in the fill factor, short-circuit photocurrent, and open-circuit voltage.